Efektivitas Program Posyandu Dalam Meningkatkan Kesadaran Dan Partisipasi Kesehatan Masyarakat - Muhammad Haris; Ahmad Maulana Anshori (UIN Siber Syekh Nurjati Cirebon, 2024)
This research aims to explore the effectiveness of the posyandu program in increasing public health awareness and participation. The method used is descriptive qualitative research by collecting primary data through observation and interviews, as well as secondary data from related literature. The research results show that the posyandu program has a significant positive impact. Public perception of this program is generally positive, with the assessment that the counseling and information provided really helps meet community needs. This program has succeeded in increasing health awareness through routine education about health, nutrition and child development, as well as health services such as examinations, immunizations and early detection of disease. Community participation is also good, as can be seen from participation in routine examinations and immunizations. Factors that influence this participation include service quality, increased knowledge, family support, accessibility, positive interactions with staff, availability of resources, trust in services, government policies, and positive user experiences.